Implikasi Konseptual Sila Kedua Pancasila Terhadap Harmoni Sosial - Joy Novi Yanti Lumbantobing; Yakobus Ndoda (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This research explores the conceptual implications of the Second Principle of Pancasila for social harmony in Indonesia. Pancasila, as the state's philosophical and ideological foundation, emphasizes the importance of "just and civilized humanity". However, the implementation of these values ​​often faces obstacles such as differences of opinion and personal interests, as well as the inability to resolve conflicts peacefully. Through a qualitative approach with literature studies and conceptual analysis, this research highlights the complexity of implementing the Second Principle and efforts to strengthen social harmony. The results show that education about Pancasila values, strengthening law enforcement institutions, and building a culture of inclusion and dialogue are important to improve the implementation of the Second Principle and create a more just and civilized society.